Wall Decoration of Early Byzantine Churches and Synagogues in the Eastern Mediterranean - Vitto, Fanny (Actual Problems of Theory and History of Art, 2019)
Very few remains of wall decoration have been preserved in situ in the Early Byzantine churchesand synagogues of the Eastern Mediterranean. Writings of Church Fathers contain descriptions of elaborate wall mosaics and paintings in churches of the Holy Land which make up to some extent for the dearth of material evidence. Concerning the synagogues, there is only a laconic allusion to wall decoration in the Jerusalem Talmud which does not give any indication of what may be represented. Excavations of Palestinian churches have yielded evidence of both wall mosaics and polychrome wall paintings which represent mostly saints, the Virgin and scenes of the Transfiguration. In synagogues, the few preserved wall paintings consist of simple geometric and stylized plant motifs, as well as texts in Aramaicwhich are dedicatory in nature or connected with the service in the synagogue. Despite the scarcity of evidence, it is possible to discern significant differences between wall decorationin churches and in synagogues. One of the reasons is the difference of attitudes of the two religions towards images, the prohibition of treading upon human figures of the Holy Scriptures in Christianity, and the prohibitionof treating images as idols in Judaism. Another reason is the difference in the people who attended the religious services, a mostly local and long-established population in the synagogues whereas, in the churches,the body of worshippers was still in the making and the lavish decoration of the churches was intended to attract new converts and teach the Holy Scriptures to those who were illiterate.